The Effect of Teaching-Learning Environments on Student's Engagement with Lean Mindset - Rasoul Khandan; Lucas Shannon (MDPI AG, 2021)
Lean thinking is a methodology employed initially by manufacturing organizations such as Toyota and New Balance that aims to increase customer value whilst also maintaining a low level of waste. The Lean thinking tools and techniques employed in the manufacturing sector can also be transferred to other sectors and significantly improve the service or product, such as public sector organizations or Higher Education Institutions (HEI). In the current education climate, due to the pandemic (SARS-CoV-2, COVID-19), the majority of HEIs have moved to an online or hybrid teaching and learning environment. This has developed the principle that Lean thinking can be deployed in educational methods and techniques to greatly increase the level of student engagement and the efficiency of learning. The following study outlines the key waste sources found in three types of teaching-learning environments (face to face, online and hybrid) and provides practical implications to counter the non-value-added issues. The data for this study were gathered through a questionnaire from final year undergraduate engineering students. The results indicate that online teaching had the greatest effect on student engagement, based on the identification and weighted values of non-value-added issues. The study highlights the key Lean wastes within online, hybrid and face to face teaching, and provides key examples within the stated Lean waste to provide solutions to improve student engagement.